2018
DOI: 10.1159/000493977
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Diagnostics, Surgical Treatment, and Prognostic Factors for Outcomes in Medullary Thyroid Carcinoma in Norway: A Nationwide Population-Based Study

Abstract: Background: Medullary thyroid carcinoma (MTC) is rare. Nationwide population-based studies are important to evaluate its clinical course. Objectives: To describe all patients with MTC in Norway during 1994–2016 and compare time-related trends in diagnostics and surgical treatment, including prognostic factors for biochemical cure and disease-specific survival (DSS). Methods: This retrospective population-based cohort study includes data for 228 out of 237 patients (96%) with MTC; 201 patients were surgically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…Patients achieving biochemical cure had a median of 2 versus 16 metastases at initial operation, and 4 versus 12 metastases at repeat surgery, compared with patients without biochemical cure. These data compare favourably against corresponding median values of 3·5 versus 10 node metastases from the Norwegian national registry, and against absolute thresholds of four node metastases for biochemical cure from the Danish national registry. The number of node metastases was also more powerful in predicting biochemical cure than MLNR or AJCC node category.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Patients achieving biochemical cure had a median of 2 versus 16 metastases at initial operation, and 4 versus 12 metastases at repeat surgery, compared with patients without biochemical cure. These data compare favourably against corresponding median values of 3·5 versus 10 node metastases from the Norwegian national registry, and against absolute thresholds of four node metastases for biochemical cure from the Danish national registry. The number of node metastases was also more powerful in predicting biochemical cure than MLNR or AJCC node category.…”
Section: Discussionmentioning
confidence: 76%
“…Of note, median MLNRs were 0·05–0·08 for patients who were biochemically cured and 0·23–0·28 for those not cured. Corresponding median MLNRs reported from a Norwegian registry study were 0·19 for patients who were biochemically cured and 0·43 for those who were not cured. In this respect, it is noteworthy that two to three times more nodes (median 57·5–64) were removed in the present study than in the Norwegian national registry (median 19–26).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…High-resolution ultrasonography is routinely used in the preoperative setup for PHPT patients, while measurements of serum calcitonin are not (64). In some patients the preoperative serum calcitonin will likely be measured as a consequence of thyroid nodules found by ultrasonography (65,66,67,68,69). Some authors have suggested systematically preoperative calcitonin measurements in patients with apparently sporadic PHPT to exclude potential MEN 2 cases (70).…”
Section: Limitationsmentioning
confidence: 99%